Toward a structural understanding of Clostridium difficile toxins A and B - Pruitt, Rory N.; Lacy, D. Borden (Frontiers in Cellular and Infection Microbiology, 2012)
Clostridium difficile is a toxin-producing bacterium that is a frequent cause of hospital-acquired and antibiotic-associated diarrhea. The incidence, severity, and costs associated with C. difficile associated disease are substantial and increasing, making C. difficile a significant public health concern. The two primary toxins, TcdA and TcdB, disrupt host cell function by inactivating small GTPases that regulate the actin cytoskeleton. This review will discuss the role of these two toxins in pathogenesis and the structural and molecular mechanisms by which they intoxicate cells. A focus will be placed on recent publications highlighting mechanistic similarities and differences between TcdA, TcdB, and different TcdB variants.